T146. Trends in epilepsy surgery at Duke University Medical Center. (May 2018) - Sinha, Saurabh R.; Allen, Jasmine; Luedke, Matthew
Abstract : Introduction: Duke University Hospital and the nearby Durham Veterans Affairs Medical Center have had an active epilepsy surgery since the 1970s. The volume and types of surgeries performed have been impacted by many factors, including personnel, available technology and techniques. Here we present a retrospective analysis of surgical epilepsy at Duke from its origins through 2017. Methods: The Duke Epilepsy Monitoring database (prospectively maintained since 2010) was augmented by paper and electronic records to obtain a nearly complete picture of epilepsy surgery procedures at Duke. Types of surgeries (intracranial monitoring with grids/strips/depths, stereoelectroencephalography (SEEG), resections – including location, thermal ablation, implantation of neurostimulators and others) were determined by year. These will put into context of personnel (especially surgeons and epileptologists), available technology and techniques, and wider trends in epilepsy surgery. Results: Over 550 patients have surgically treated for epilepsy at out institution (not including neurostimulator implantations). Several general trends have emerged in the data – over time the percentage of patients who undergo intracranial monitoring as part of their surgical evaluation has gone up as compared to resection without intracranial monitoring. More recently, there has been a shift towards SEEG and away from grids/strips. Furthermore, thermal ablation has rapidly replaced open anterior temporal lobectomy for mesial temporal lobe epilepsy. Neurostimulator implantation volumes have also increased over time, especially in the pediatric population. This change and overall volumes appear to be mostly related to personnel changes and growth. Conclusion: A wide variety of factors (both internal and external) have contributed to trends in epilepsy surgery at Duke University Medical Center. Emergence of technologies like laser ablation of epileptogenic tissue have altered approaches to certain patients, such as mesial temporal lobe epilepsy. External trends, like the emergence of SEEG in the U.S., have altered the approach to intracranial monitoring. The availability of specific personnel has also impacted both the volume and types of procedures being performed.